Safety and efficacy of the combination of nivolumab plus ipilimumab in patients with melanoma and asymptomatic or symptomatic brain metastases (CheckMate 204). Issue 11 (21st April 2021) - Tawbi, Hussein A; Forsyth, Peter A; Hodi, F Stephen; Lao, Christopher D; Moschos, Stergios J; Hamid, Omid; Atkins, Michael B; Lewis, Karl; Thomas, Reena P; Glaspy, John A; Jang, Sekwon; Algazi, Alain P; et al.
Abstract: Background: In patients with melanoma and asymptomatic brain metastases (MBM), nivolumab plus ipilimumab provided an intracranial response rate of 55%. Here, we present the first report for patients who were symptomatic and/or required corticosteroids and updated data for asymptomatic patients. Methods: Patients with measurable MBM, 0.5-3.0 cm, were enrolled into Cohort A (asymptomatic) or Cohort B (stable neurologic symptoms and/or receiving corticosteroids). Nivolumab, 1 mg/kg, and ipilimumab, 3 mg/kg, were given intravenously every 3 weeks ×4, followed by nivolumab, 3 mg/kg, every 2 weeks until progression, unacceptable toxicity, or 24 months. The primary endpoint was intracranial clinical benefit rate (CBR; complete response [CR], partial response [PR], or stable disease ≥6 months). Results: Symptomatic patients (N = 18) received a median of one nivolumab and ipilimumab combination dose and had an intracranial CBR of 22.2%. Two of 12 patients on corticosteroids had CR; 2 responded among the 6 not on corticosteroids. Median intracranial progression-free survival (PFS) and overall survival (OS) were 1.2 and 8.7 months, respectively. In contrast, with 20.6 months of follow-up, we confirmed an intracranial CBR of 58.4% in asymptomatic patients (N = 101); median duration of response, PFS, and OS were not reached. No new safety signals were observed. Conclusions: Nivolumab plus ipilimumab provides durable clinical benefit for asymptomatic patients with MBM and should be considered for first-line therapy. This regimen has limited activity in MBM patients with neurologic symptoms and/or requiring corticosteroids, supporting the need for alternative approaches and methods to reduce the dependency on corticosteroids. Clinical trial registration. ClinicalTrials.gov, NCT02320058.